Tetrazolium test for the viability of gherkin seeds - Paiva, Emanoela; Torres, Salvador; Almeida, João Paulo; Sá, Francisco Vanies; Oliveira, Renata Ramayane (Revista Ciência Agronômica, 2016)
The tetrazolium test is a quick and effective method for evaluating viability in seeds. The aim of this study was to determine a methodology for using the tetrazolium test, and its efficiency in verifying viability in seeds of the gherkin (Cucumis anguria L.). Consequently, five batches of gherkin seed were initially evaluated by the tests for germination, first count and speed of germination. The batches were then subjected to treatments in order to adjust the methodology for the tetrazolium test, evaluating three concentrations of tetrazolium solution (0.100, 0.075 and 0.050%), kept in the dark for two, four and six hours, under temperatures of 35 °C and 40 °C, with four replications of 25 seeds per treatment. At the end of the staining period, the seeds were washed in running water, split lengthways between the cotyledons, and classified as viable and non-viable. Evaluation of viability in seeds of the gherkin by tetrazolium test is efficient when carried out at a concentration of 0.050%, either for six hours at 35 °C or four hours at 40 °C.